PENGARUH LEADERSHIP STYLE TERHADAP FINANCIAL PERFORMANCE MELALUI INNOVATION DAN CUSTOMER LOYALTY PADA SEKTOR RETAIL DI SURABAYA - Denanda Natalia Lestari; Devie Devie (Business Accounting Review, 2016)
This study aimed to examine the direct and significant affect of leadership style to innovation, innovation to customer loyalty, customer loyalty ro financial performance, innovation to financial performance , and leadership style to financial performance on retail firms in Surabaya. This study also aimed to examine the indirect and significant affect of leadership style to financial performance through innovation and customer loyalty. This study used quantitative approach, and the data obtained by distributing questioner and financial report to retail firms in Surabaya. The sample used in this study was 18 retail firms in Surabaya listed in BEI 2012-2014, with each 10 employess and 10 customers of each firm. The data obtained processed by using smartPLS software.The result showed that there was positive and significant relationship of leadership style to innovation, innovation to customer loyalty, customer loyalty to financial performance, and leadership style to financial performance, but negative and significant relationship of innovation to financial performance on retail firms in Surabaya. Innovation and customer loyalty became as the intervening variables to leadership style and financial performance because the direct relationship between leadership style and financial performance gave larger affect than through innovation and customer loyalty.